Education and Early Detection of Non-Communicable Diseases in The Tanjung Selor Community, North Kalimantan - Nur Fadillah Putri; Atika Apriati; Selly Marlina; Nur Amanah Lungita; Nida Amalia; Sri Sunarti; Ghozali Ghozali; Suprayitno Suprayitno (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2023)
Non-communicable diseases are diseases that cannot be transmitted to other people and the stages of disease development are slow and chronic. Most non-communicable diseases are not accompanied by symptoms, so many do not know and are aware that they have a non-communicable disease. This activity aims to provide education about the importance of preventing and controlling PTM through a healthy lifestyle and regular health checks using lecture and discussion methods. Education is carried out for teenagers to the elderly who are at risk of contracting non-communicable diseases in Tanjung Selor, North Kalimantan. The implementation of the activities ran smoothly and received good responses from the target. After the implementation of the activity, it was seen that there was a positive change in the target related to knowledge by conducting a qualitative pretest-posttest asking participants directly orally and awareness of the importance of health checks for the prevention and control of non-communicable diseases. Health workers are expected to be able to provide education and monitor the prevention and control of non-communicable diseases and the importance of paying attention to public health, especially for the elderly, who are a group at risk of experiencing non-communicable diseases.